Modification and transfer into an embryonal carcinoma cell line of a 360-kilobase human-derived yeast artificial chromosome. - Pavan, W J (1990)
A neomycin resistance cassette was integrated into the human-derived insert of a 360-kilobase yeast artificial chromosome (YAC) by targeting homologous recombination to Alu repeat sequences. The modified YAC was transferred into an embryonal carcinoma cell line by using polyethylene glycol-mediated spheroplast fusion. A single copy of the human sequence was introduced intact and stably maintained in the absence of selection for over 40 generations. A substantial portion of the yeast genome was retained in hybrids in addition to the YAC. Hybrid cells containing the YAC retained the ability to differentiate when treated with retinoic acid. This approach provides a powerful tool for in vitro analysis because it can be used to modify any human DNA cloned as a YAC and to transfer large fragments of DNA intact into cultured mammalian cells, thereby facilitating functional studies of genes in the context of extensive flanking DNA sequences.